Improved solubility of telmisartan by using freeze-dried solid dispersion method - Aljapairai, Khater Ahmed Saeed; Chatterjee, Bappaditya (2017)
Introduction: Drugs with poor water solubility often result in low dissolution and consequently reduced bioavailability. Telmisartan is an angiotensin II receptor antagonist, which is used in the prevention and treatment of hypertension. One of the major problems with this drug is it has poor water solubility that lead to its low bioavailability. Objective: The aim of this study is to improve solubility of telmisartan by using freeze-dried solid dispersion (SD) method. Methods: PVP K30 was selected as carrier and sodium carbonate (Na2CO3) as pH modifier for the formulation. After checking the compatibility between all ingredients by differential scanning calorimetry (DSC) and attenuated total reflectance spectroscopy (ATR-FTIR), the SD was prepared by using freeze-dried method (Martyn Christ, Germany). The selected drug: carrier ratios were 1:3, 1:5, and 1:10 (w/w). The SD powders were evaluated for aqueous solubility. Telmisartan concentration was measured by a high performance liquid chromatographic system (HPLC) with UV detector at 231 nm wavelength. Results: The SD containing telmisartan: PVP K30 (1:5) showed the highest solubility (151.46 µg/ml), followed by 1:10 (121.37 µg/ml) and 1:3 (114.48µg/ml). Na2CO3 played important role to enhance telmisartan solubility by alkalinizing the formulation which is proved by comparing SD prepared with and without Na2CO3. The conversion of crystalline telmisartan to amorphous by freeze drying might be the factor behind improved solubility. This is established by DSC and X-ray diffraction (XRD) studies. Conclusion: We suggest the prepared telmisartan solid dispersion by using freeze -dried method shall improve solubility of the drug and can be formulated as final dosage form such as tablet or capsule after relevant pre-formulation studies.